2011
DOI: 10.1002/j.2055-2335.2011.tb00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Therapeutic Medication Omissions: Incidence and Predictors at an Australian Hospital

Abstract: Background:The inconsistent definition of non-therapeutic medication omissions, under-reporting, and a poor understanding of their associated factors hamper efforts to improve medication administration practices. Aim: To examine the incidence of non-therapeutic medication omissions among acutely ill medical and surgical adult patients; and to identify the patient-, drug-and system-related predictors of these omissions. Method: A medication chart audit of 288 acutely ill adult medical and surgical patients admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 16 publications
(46 reference statements)
3
29
4
Order By: Relevance
“…) and medication errors (Latimer et al . ). Our study found male participants were less frequently repositioned compared with females.…”
Section: Discussionmentioning
confidence: 97%
“…) and medication errors (Latimer et al . ). Our study found male participants were less frequently repositioned compared with females.…”
Section: Discussionmentioning
confidence: 97%
“…team, task, environment, individual and system factors) (Deans, 2005;Evans, 2009;Popescu et al, 2011;Roughead and Semple, 2009) associated with the complex process of medication administration, rather than individual or professional group factors (Roughead and Semple, 2009). Reported factors that increase the likelihood of a medication error occurring include knowledge-based mistakes, poor communication (Nichols et al, 2008), polypharmacy, and poor compliance with medication assessment practices such as medication reconciliation (Latimer et al, 2011). The aim of this study, conducted at an Australian university, was to examine Bachelor of Nursing (BN) student's perceived effectiveness of an educational intervention which promotes a systems approach to understanding medication adverse events and errors, as well as strategies to avoid such errors.…”
Section: Introductionmentioning
confidence: 96%
“…Using 2011e12 Australian hospital admission data, of the 9.3 million separations it is estimated there are 230,000 medication related hospital admissions every year, costing the community approximately $1.2 billion annually (Roughead et al, 2013). Medication errors can occur during the phases of prescribing, dispensing, and administration, with system and human factors increasing the likelihood of an error or omissions (Evans, 2009;Latimer et al, 2011). Whilst medication administration is a routine task for nursing, it is becoming an ever increasingly complex activity.…”
Section: Introductionmentioning
confidence: 99%
“…Omitted medications have been found to constitute a large proportion of medication administration errors . Dose omissions have been reported to occur in 4.2% to 30% of doses audited …”
Section: Introductionmentioning
confidence: 99%
“…4 Dose omissions have been reported to occur in 4.2% to 30% of doses audited. 3,[5][6][7] Electronic medication management systems (eMMS), implemented in both inpatient and outpatient settings, have been reported to improve medication safety associated with medication prescribing and administration. 8,9 Common causes of medication errors related to prescribing include medication nomenclature similarities (look-alike, sound-alike), illegible handwriting, transcription errors, inappropriate abbreviations, and inaccurate dose calculations.…”
Section: Introductionmentioning
confidence: 99%